2017
DOI: 10.3892/or.2017.5737
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 expression is elevated in head and neck cancer and inhibition of protein arginine methylation by adenosine dialdehyde or PRMT1 knockdown downregulates proliferation and migration of oral cancer cells

Abstract: Protein arginine methylation is a post-translational modification that has been implicated in signal transduction, gene transcription, DNA repair and RNA processing. Overexpression or deregulation of protein arginine methyltransferases (PRMTs) have been reported to be associated with various cancers but have not been studied in head and neck cancer (HNC). We investigated the involvement of the modification in HNC using oral cancer cell lines (SAS, OECM-1 and HSC-3) and an immortalized normal oral cells (S-G). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…Recent reports have revealed the relationship between various cancers and PRMT1, which is overexpressed in breast cancer, bladder cancer and lung cancer [17][18][19][20].. Notably, PRMT1 was recently reported to be upregulated through miR-503 in HCC [21], and PRMT1 may promote the proliferation and metastasis of HCC cells in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed the relationship between various cancers and PRMT1, which is overexpressed in breast cancer, bladder cancer and lung cancer [17][18][19][20].. Notably, PRMT1 was recently reported to be upregulated through miR-503 in HCC [21], and PRMT1 may promote the proliferation and metastasis of HCC cells in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in arginine methylation of RG/RGG-containing proteins is associated with a plethora of neurodegenerative diseases and cancers (11,13,48,63,(78)(79)(80). In line with this, PRMT1 mRNA levels are increased in several cancer cells and tumors (81)(82)(83). Moreover, PRMT1 has been shown to regulate epithelial-mesenchymal transition, cancer cell migration, and invasion, which are hallmarks of cancer progression and metastasis (84).…”
Section: Tnpo1 and Tnpo3 Suppress Cirbp Phase Separation And Stressmentioning
confidence: 91%
“…PRMT1 is known to promote proliferation of many cancer cell lines in vitro and in vivo , ( 16,17,20‐22 ) including hepatoma cell lines. We confirmed that PRMT1 inhibition using a small molecule inhibitor, protein arginine methyltransferase inhibitor, reduced hepatoma cell proliferation under normal conditions.…”
Section: Resultsmentioning
confidence: 99%